(untitled) (ACME, 2021)
In the Ancient world people thought that there were particular natural energies which related the different elements of the universe. A special link was the one between plants, stones, animals and the seven planets (which included also the Sun and the Moon). These correspondences with the stars are highlighted in some pamphlets published in the Catalogus Codicum Astrologorum Graecorum, which comprehends some excerpta from the astrological manuscripts of the most important European libraries. This article’s aim is to talk about these different pamphlets and to show the link between the natural elements and the planets, in particular relating the Moon. The characteristics and the uses of the plants, stones and animals associated to this planet will complete the dissertation, in order to show some ancient natural-magic rituals.